γ-Aminobutyric acid as a biomarker of the lateralizing and monitoring drug effect in patients with magnetic resonance imaging-negative temporal lobe epilepsy - Wu, Shuohua; Wang, Qianqi; Zhai, Huige; Zhang, Yiwen; Xu, Dongyuan; Yan, Gen; Wu, Renhua (Frontiers in Neuroscience, 2023)
Introduction: Despite verifying proton magnetic resonance spectroscopy (1H-MRS) for focal localization in magnetic resonance imaging (MRI)-negative temporal lobe epilepsy (TLE), it is necessary to illustrate metabolic changes and screen for effective biomarkers for monitoring therapeutic effect. We used 1H-MRS to investigate the role of metabolic levels in MRI-negative TLE. Materials and methods: Thirty-seven patients (n = 37,14women) and 20 healthy controls (n = 20,11 women) were investigated by 1H-MRS. We compared the metabolite level changes in the epileptic and contralateral sides on the mesial temporal and dorsolateral prefrontal cortices and analyzed their association with clinical symptoms. Results: γ-Aminobutyric acid (GABA) levels were significantly lower on the epileptic side （2.292 ± 0.890） than in the contralateral side (2.662 ±0.742, P = 0.029*） in patients on the mesial temporal lobe. N-acetylaspartate (NAA) levels were significantly lower on the epileptic side （7.284 ± 1.314） than on the contralateral side (7.655 ±1.549, P = 0.034*). NAA + N-acetylaspartylglutamate levels were significantly lower on the epileptic side （7.668 ± 1.406） than on the contralateral side (8.086 ± 1.675, P = 0.032*). Glutamate levels were significantly lower on the epileptic side (7.773 ± 1.428) than on the contralateral side (8.245 ± 1.616, P = 0.040*). Moreover, a significant negative correlation was found between GABA levels in the epileptic mesial temporal lobe and tonic-clonic seizure frequency (r= –0.338, P = 0.046*). Conclusions: GABA is a potential biomarker for lateralization and monitoring seizure frequency in MRI-negative TLE.